Lifelong intake of flaxseed or menhaden oil to provide varying n‐6 to n‐3 PUFA ratios modulate bone microarchitecture during growth, but not after OVX in Sprague–Dawley rats. Issue 8 (9th March 2017) - Longo, Amanda B.; Sullivan, Philip J.; Peters, Sandra J.; LeBlanc, Paul J.; Wohl, Gregory R.; Ward, Wendy E.
Abstract : To determine the impact of n‐3 PUFA source and the n‐6 to n‐3 PUFA ratio on bone structure in the rat model of postmenopausal osteoporosis, diets are provided during growth and after OVX to reflect the fact that humans consume PUFA throughout life. While diet‐induced differences in bone structure during are were not maintained following OVX, diet does modulate trabecular bone in SHAM and cortical bone in OVX rats. Dietary PUFA modulates some bone structure outcomes during growth, but at the quantities studied, is not an effective preventive strategy against OVX‐induced trabecular bone loss. Abstract : Scope: Skeletal health is a lifelong process impacted by environmental factors, including nutrient intake. The n‐3 source and PUFA ratio affect bone health in growing rats, or following ovariectomy (OVX), but no study has investigated the longitudinal effect of PUFA‐supplementation throughout these periods of bone development. Methods and results: One‐month‐old, Sprague–Dawley rats ( n = 98) were randomized to receive one of four diets from 1 through 6 months of age. Diets were modified from AIN‐93G to contain a varying amount and source of n‐3 (flaxseed versus menhaden oil) to provide an n‐6 to n‐3 ratio of 10:1 or 5:1. At 3 (prior to SHAM or OVX) and 6 months of age, bone microarchitecture of the tibia was quantified using in vivo micro‐computed tomography (SkyScan 1176, Bruker microCT). Providing 5:1 (flaxseed) resulted in lower trabecular thickness and medullary area and greater cortical area fraction during growth compared to diets with a 10:1 PUFA ratio, but many of these differences were not apparent following OVX. Conclusion: PUFA‐supplementation at levels attainable in human diet modulates some bone structure outcomes during periods of growth, but is not an adequate strategy for the prevention of OVX‐induced bone loss in rats